Effect of body weight reduction on stress and recovery among Brazilian judokas - Fortes, L. S.; Lira, H. A. A. S.; Mendonça, L. C. V.; Paes, P. P.; Vianna, J. M.; Pérez, A. J. (International Journal of Sport and Exercise Psychology, 2019)
Purpose: The aim of the study was to compare the magnitude of the symptoms of stress and the perception of psychophysiological recovery among judokas who adopted methods for body weight reduction and those who did not adopt such methods. Method: Participants included 39 judokas who were selected in a non-probabilistic way. The participants were randomly divided into two groups, namely, an experimental group (EG, n = 21) and a control group (CG, n = 21). The EG was induced to adopt an increase in the frequency of strategies directed towards body weight reduction, whereas the members of the CG followed their normal behaviour patterns. The Daily Analysis of Life Demands for Athletes was used to evaluate the symptoms of stress. The Recovery-Stress Questionnaire for Athletes was used to evaluate the perception of psychophysiological recovery. Results: The findings revealed that the magnitude of the symptoms of stress increased in the EG (F(2, 18) = 43.63, p = .01), whereas they did not increase in the CG (F(2, 17) = 3.14, p = .18). Furthermore, the post-test revealed significant differences between the two groups (F(2, 37) = 38.55, p = .01). The results demonstrated a reduction in the perception of psychophysiological recovery in the EG (F(2, 18) = 69.97, p = .001) and an increase in the CG (F(2, 18) = 47.61, p = .01), with a statistically significant difference between the two groups (F(2, 37) = 116.75, p = .001). Conclusions: It was concluded that body weight reduction increased the magnitude of stress symptoms and reduced the perception of psychophysiological recovery in judokas.